Ability to organize experiential activities of teachers in primary schools - Ngoc , Nguyen Thi (Journal of Education and e-Learning Research, 2024)
This study examines the capacity of primary school teachers to design, organize, and evaluate experiential activities, utilizing a robust measurement framework grounded in the 2018 General Education Program. The evaluation encompasses 540 teachers, drawing on diverse sources, including questionnaires, regulatory documents, and input from educational stakeholders. The findings highlight commendable strengths in planning and organizing experiential activities, with 324 teachers demonstrating excellent or good capacity. However, critical gaps are evident, particularly in contextual analysis, testing tool design, and information processing, reflecting a need for targeted professional development. The measurement framework, calculated with a distance value of 0.8, employs a scale categorization that offers nuanced insights into the varying impact of experiential activities. The study underscores the significance of targeted professional development initiatives tailored to address identified gaps. Curriculum adaptations are recommended to leverage successful strategies, and informed decision-making is facilitated by evidence-based policies. The findings advocate for a culture of continuous improvement in educational practices. While the study provides valuable insights, limitations include contextual specificity, potential subjectivity in self-reported data, and the exclusion of student perspectives. A quantitative emphasis, reliance on a single methodology, and a sample size of 540 teachers may impact generalizability. This research informs educational stakeholders, policymakers, and practitioners about the current state of experiential education in primary schools. The study, within its limitations, contributes actionable insights to enhance the effectiveness of teacher training and curriculum design, fostering an environment conducive to experiential learning practices.